2009
DOI: 10.2514/1.37848
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigation of a Nonslender Delta Wing

Abstract: Computational simulations have been performed for a 50-deg-sweep delta wing with a sharp leading edge at a 15 deg angle of attack and moderate Reynolds numbers of Re 2 10 5 , Re 6:2 10 5 , and Re 2 10 6 . A sixthorder compact-difference scheme with an eighth-order low-pass filter is used to solve the Navier-Stokes equations. Turbulence modeling has been accomplished using an implicit large eddy simulation method that exploits the highorder accuracy of the compact-difference scheme and uses the discriminating h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 33 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…We do not take into account the effects of the enhanced turbulent mixing and boundary layer effects at higher Reynolds numbers. However, the LEV has been found to be very resilient to the effects of Reynolds numbers [23]. Therefore, while this investigation does not provide a quantitative description of the full-scale flow, it enables the understanding of the key features of downwind sail flow.…”
Section: Overview Of the Present Workmentioning
confidence: 95%
“…We do not take into account the effects of the enhanced turbulent mixing and boundary layer effects at higher Reynolds numbers. However, the LEV has been found to be very resilient to the effects of Reynolds numbers [23]. Therefore, while this investigation does not provide a quantitative description of the full-scale flow, it enables the understanding of the key features of downwind sail flow.…”
Section: Overview Of the Present Workmentioning
confidence: 95%
“…For the same wing model at the same incidence angle, Hahn and Drikakis ( 9 , 10 ) found that an implicit large eddy simulation is more accurate than hybrid RANS/LES at the region close to the wing tip, but some features of the flow are still different from the experimental data. By combining computational and experimental work, Gordnier et al ( 11 ) examine the flow structures over a 50-deg-swept plane delta wing at 15°. Further computations are still needed to fully understand transitional or turbulent flow.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Computations of the flow structure on delta wings of low sweep angle, with emphasis on lower values of Reynolds number, have been performed by Gordnier and Visbal [21] using a high-order, structured-grid, finite difference algorithm [22]. Gordnier and Visbal [23] and Gordnier et al [24] have also addressed features of the flow structure of planar delta wings at moderate values of Reynolds number.…”
mentioning
confidence: 99%